Organoid model of urothelial cancer: establishment and applications for bladder cancer research - Terry Whyard; Jingxuan Liu; Frank S Darras; Wayne C Waltzer; Victor Romanov (BioTechniques)
3D cancer cell models are suitable for drug evaluation because they more precisely mimic tissue architecture than 2D cultures. To study cytotoxicity of anticancer agents, the most sensitive CellTiter-Glo 3D assay is used. However, this is an end point assay, so it is not possible to consider the variance of the starting material amount in the final reading. It is difficult to maintain an even plating density of 3D organoids for cytotoxicity analysis. We present a simple, 3D bladder cancer culture that can be maintained, cryopreserved and used for molecular and drug response studies. We applied a simple modification of the drug response assay for 3D cultures by measuring the background signal with the CellTiter Blue assay before drug application.